Tin Oxide (SnO₂) Nanoparticles in Modern Medicine: Development, Standardization, and Therapeutic Applications - Omkar Dnyaneshwar Chavan; Dr. Deepak D. Sonawane; Mayuri P. Pol (Asian Journal of Pharmaceutical Research and Development, 2026)
Tin dioxide nanoparticles (SnO₂) represent an extremely versatile class of metal oxide nanomaterials with vast potential in a broad spectrum of modern medical applications. The key characteristics of tin dioxide nanoparticles include high optical bandgap energy ( 3.6 eV), rutile crystal phase structure, elevated surface area to volume ratio, remarkable chemical stability, and controllable surface chemistry. Thus, tin dioxide nanoparticles display an excellent array of optical, electrical, and biological properties enabling their exploitation for numerous medical purposes. The current review article offers a systematic investigation of physicochemical properties, synthesis techniques, characterization procedures, standardization criteria, and various biomedical applications of tin dioxide nanoparticles with particular focus on advancements published from 2020 to 2026. Different synthesis techniques (physical processes, such as laser ablation and vapor deposition; chemical synthesis, namely sol-gel process, hydrothermal treatment, co-precipitation, microemulsion; and green synthesis using plants and microorganisms) are analyzed in terms of the underlying mechanism, particle size, shape, and scalability. The mechanisms responsible for the interaction of tin dioxide nanoparticles with biological entities (cellular uptake, protein corona, reactive oxygen species, and apoptosis) are presented in detail. The range of therapeutic applications includes antitumor activity, antibacterial effect, controlled drug delivery, biosensor applications, and anti-inflammatory and antioxidant activities. Toxicology data, which includes in vitro toxicity studies, genotoxicity studies, and in vivo organ toxicity data, is carefully evaluated to demarcate the therapeutic window and determine safety limits. Advances in the field such as functionalized nanoparticles, graphene-SnO₂ nanocomposites, doping techniques, and stimuli-responsive drug delivery systems have been mentioned. In conclusion, the paper identifies the critical issues that hamper the clinical application of SnO₂-based nanoparticles and discusses future research directions, particularly related to artificial intelligence, personalized nanomedicines, and GMP-based manufacture.